Study of the leaching process of precious metals from waste electrical and electronic equipment - Dias, João Alberto Gomes Ferreira (2023)
The development of modern society is anchored in the advancement of technology, and as a collateral consequence, waste from electrical and electronic equipment (WEEE) is increasing rapidly. This alarming trend poses a serious concern for the depletion of our planet's resources, as the extraction of elements such as metals from the Earth's crust intensifies, pollution and stress on ecosystems increases. Nevertheless, WEEE still hold significant potential, particularly in recycling valuable elements like precious metals and base metals. Recycling these materials can offer substantial economic and environmental benefits, making it a crucial aspect in the circular economy. Common processes for metal recovery from WEEE often rely on classic establish techniques such as pyrometallurgy, which raises concerns about energy consumption and pollution, or classic hydrometallurgy, using aggressive solvents harmful to humans and the environment leading stakeholders to seek alternatives, more eco-friendly lixiviants to ensure sustainable and responsible metal recovery. The work intended to shed some light in the leaching ability of more sustainable agents on printed circuit boards (PCB) and compare their efficiency in the leaching process with classical approaches. Silver recovery from Printed Circuit Boards (PCBs) using thiourea, thiosulfate and sulfuric acid as leaching agents, was studied to compare the effectiveness of alternative leaching agents and validate the methodology. Quantification was performed by Inductively Coupled Plasma-Atomic Emission Spectroscopy and AAS atomic absorption spectroscopy. Sulfuric acid as predicted was the most effective lixiviant (99,7% yield) followed by Ammonium thiosulfate (72,5% yield) on silver powder samples. In PCBs and complex samples, the use of thiosulfate and thiourea solutions for silver extraction, under the tested conditions, did not show promising results, requiring more studies.